The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.36510/learnland.v15i1.1081
|View full text |Cite
|
Sign up to set email alerts
|

A Spotlight on Research-Based Theatre

Abstract: “Tell me about your research.” How does one begin to convey the importance of our life’s work—our research? Enter stage right, Research-based Theatre, an innovative, arts-based methodology that takes research data and brings it to life, by showing, rather than telling. In this article, we tell the story of how Research-based Theatre first came to be, and why it is especially well suited to the contemporary challenge of showcasing diverse and marginalized voices. We also share a short scene that illustrates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…As an RbT product, Larry positioned itself in the relatively unfrequented top-left corner of the spectrum, being an aesthetic performance with systematic research as its primary source. Some have suggested that RbT typically subordinates aesthetics to pragmatic aims [ 52 ]; in contrast, some practitioners defend the opposite approach [ 11 ]. For example, Schneider and colleagues (2014) argued that to generate drama capable of engaging a wide audience required a “creative and imaginative process… unconstrained by ‘worthy’ or didactic aims.” (p. 62) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an RbT product, Larry positioned itself in the relatively unfrequented top-left corner of the spectrum, being an aesthetic performance with systematic research as its primary source. Some have suggested that RbT typically subordinates aesthetics to pragmatic aims [ 52 ]; in contrast, some practitioners defend the opposite approach [ 11 ]. For example, Schneider and colleagues (2014) argued that to generate drama capable of engaging a wide audience required a “creative and imaginative process… unconstrained by ‘worthy’ or didactic aims.” (p. 62) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This reflection suggests that, in general, ambiguity increases as a research-based theatre piece approaches the aesthetic end of Beck and colleagues’ (2011) performance continuum [ 37 ]. We view this not as an argument against aesthetic performances but rather in favour of the pluralistic combination of knowledge translation approaches, such that each contributes its distinctive affordances [ 52 ]. ABKT in general may not be the most efficient means of conveying factual knowledge [ 54 ]; its unique value lies in such areas as the communication of findings that cannot be distilled into simple propositional statements, and the enhancement of audience interest and critical engagement [ 13 , 20 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other RbT projects centre theatre throughout the research process, using script 10 See following work for Ethnotheatre (Saldaña, 2011), research-informed theatre (Gray & Kontos, 2018), verbatim theatre (Vachon & Salvatore, 2022), applied theatre (Freebody et al, 2018) and documentary theatre (Forsyth & Megson, 2009). 11 For readings on Research-based Theatre as a methodology and approach to working with communities see Belliveau & Lea (2016), Belliveau & Sinclair (2018), Shigematsu et al (2022;. Research-based Theatre is influenced by and compliments the work in A/r/tography (LeBlanc & Irwin, 2019).…”
Section: Mohsenimentioning
confidence: 99%